Implementing open innovation using quality management systems: The role of organizational commitment and customer loyalty - Zoltán Krajcsák (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Open innovation contributes to serving the customers of organizations with higher quality, as the customers become an active part of the innovation process. A successful solution for implementing open innovation can be achieved if organizations first create a total quality management (TQM) culture and then build on this foundation an ISO 9004:2018. The success of a quality management system depends first and foremost on the attitudes of the stakeholders, and the importance of technological and other conditions is only secondary. The goal in developing a successful philosophy of TQM is to build and sustain the leaderships' and employees' commitment, while the key to the success of ISO 9004:2018 is to establish and maintain the employees' commitment and customer loyalty. The case study presented in this article demonstrates the need to increase the affective and normative commitment of leaders and employees in TQM, and after its implementation, there is a need to increase the employees' continued commitment and customer loyalty in ISO 9004:2018 in order to succeed in quality management systems and open innovation.
Keywords: 650; customer loyalty; ISO 9004:2018; open innovation; organizational commitment; TQM